2017
DOI: 10.7897/2277-4343.08252
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Potential of Some Ayurvedic Plants of North Eastern India: A Comprehensive Pharmacological Review

Abstract: The paper highlights some of the most important Ayurvedic medicinal plants of North Eastern India having anticancer potential. A brief review of distribution and pharmacological study (both in vivo and in vitro) of ten Ayurvedic medicinal plants of the region published by various researchers is illustrated in this paper. The medicinal plants discussed here are Enhydra Fluctuans Lour (Sanskrit: Hilamochika), Ageratum conizoides Linn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…There are no such side effects and, economically, the use of Ayurvedic plants. [367] This review paper thus highlights the in-vitro anthelmintic role of Bacopa monnieri in different pharmacological models. When their anthelmintic activity was conducted separately on adult Indian earth worms (Pheretima posthuman), Ghosh et al, concluded that the n-butanol fraction and ethanolic extract of Bacopa aerial parts were more potent than ethyl acetate and aqueous fractions, but the petroleum ether extract did not show anthelmintic activity when compared to the reference drugs piperazine citrate and albendazole.…”
Section: Antimicrobial Potentialmentioning
confidence: 99%
“…There are no such side effects and, economically, the use of Ayurvedic plants. [367] This review paper thus highlights the in-vitro anthelmintic role of Bacopa monnieri in different pharmacological models. When their anthelmintic activity was conducted separately on adult Indian earth worms (Pheretima posthuman), Ghosh et al, concluded that the n-butanol fraction and ethanolic extract of Bacopa aerial parts were more potent than ethyl acetate and aqueous fractions, but the petroleum ether extract did not show anthelmintic activity when compared to the reference drugs piperazine citrate and albendazole.…”
Section: Antimicrobial Potentialmentioning
confidence: 99%